SEC Rule 10b-5 (Washington University Law Quarterly, 1974)
Rule 10b-5, the most comprehensive of the antifraud provisions found in federal securities law, has been described as a proscription of “practically any sin of omission or commission which may be imagined in connection with the purchase or sale of a security.” While the essence of the rule is that it requires disclosure of material facts, it does not impose strict liability for misrepresentation or omission. The nature and extent of the additional elements of a private action under rule 10b-5 are the subject of this section. It will examine the required state of mind, “scienter,” and compare the standard established by two circuit courts of appeals. Further, it will ascertain the relationships among materiality, causation, and reliance, and assess the burden that proof of these elements places upon a plaintiff alleging fraud in connection with a securities transaction.
Keywords: Securities fraud; Scienter; Liability